Grouped Coefficients to Reduce Bias in Heterogeneous Dynamic Panel Models with Small T - Hendricks, Nathan P.; Smith, Aaron (My University, 2015)
We propose the grouped coefficients estimator to reduce bias in dynamic panels with small T that have a multilevel structure to the coefficient and factor loading heterogeneity. If groups are chosen such that the within-group heterogeneity is small, then the grouped coefficients estimator can lead to substantial bias reduction compared to pooled GMM dynamic panel estimators. We also propose using a Wald test that can be used to assess whether pooled estimators suffer from heterogeneity bias. We illustrate the usefulness of grouped coefficients with an application to labour demand in which the coefficients are grouped by sub-sector. Our results suggest that the standard pooled estimates are substantially biased.
Citation: Nathan P. Hendricks & Aaron Smith (2015) Grouped coefficients to reduce bias in heterogeneous dynamic panel models with small T, Applied Economics, 47:40, 4335-4348, DOI: 10.1080/00036846.2015.1029112
Keywords: Dynamic panel; Varying coefficient; Cross-sectional dependence; Multilevel; JEL: C23; JEL: C52